Mnemonic strategy training increases neocortical activation in healthy older adults and patients with mild cognitive impairment - Hampstead, Benjamin M. (Int J Psychophysiol, 2019)
Learning and memory deficits characterize the diagnosis of amnestic mild cognitive impairment (aMCI), which is widely viewed as a clinical precursor to Alzheimer’s type dementia. There is a growing interest in non-pharmacologic interventions, such as mnemonic strategies, for improving learning and memory in patients with aMCI as well as for maintaining functioning in healthy older adults. Using an ecologically relevant object-location association paradigm, we conducted a randomized, controlled, single-blind study in which healthy older adults and patients with aMCI were randomized to either mnemonic strategy training or a control group that was matched for stimulus exposure. We previously reported that mnemonic strategy training resulted in significantly greater learning and memory improvements compared to the matched exposure condition, in both aMCI patients and healthy controls. The current study examined changes in neocortical activation during encoding in a subset of participants who underwent functional magnetic resonance imaging (fMRI) scanning both before and after training. To minimize potential confounds in between-group comparisons, we employed non-linear cortex based alignment and included only correctly encoded stimuli in our analyses. When re-encoding stimuli learned during training (i.e., trained stimuli), we found a general enhancement of activation in right prefrontal and parietal regions, possibly reflecting practice-related improvement in coordinate spatial processing in all but the aMCI exposure group. Left hemisphere activation was typically only evident in the mnemonic strategy trained participants, regardless of diagnostic status, with the ventrolateral prefrontal cortex appearing especially important for strategy use. While encoding relatively novel stimuli, both mnemonic strategy groups (aMCI patients and healthy controls) demonstrated increased activation in a subset of regions showing change for the trained stimuli, indicating a mnemonic strategy-induced change in the processing of new information. These findings could not be explained by repeated exposure since there was little to no activation overlap in the respective exposure control groups. The current results reinforce the potential benefits of cognitive interventions in these growing populations and indicate that neuroplastic change in key rostral and lateral prefrontal regions mediate this behavioral change.